ADAPTATION AND SOCIAL MOBILITY STRATEGIES IN FACING INDUSTRIALIZATION IN RURAL COMMUNITIES - Arie Wahyu Prananta (Adisam Publisher, 2024)
The ongoing industrialization process will certainly influence the dynamics of rural community life. As a basic prerequisite for industrialization, the transfer of land from agriculture to industry causes changes in various dimensions of people's lives. The absorption of workers, especially from outside the region, also gives rise to new communities in rural areas which increasingly add to the complex patterns of social relations that are being built. In responding to the industrialization process, society develops trust, strong interactions between members, as well as new norms or rules that indicate a type of bridging social capital. The basic principle of social capital is that only groups of people who have a set of social and cultural values ​​that appreciate the importance of cooperation can progress and develop on their own. Bridging social capital owned by rural communities produces adaptive capacity. The forms of adaptive capacity developed are flexibility to maintain the sustainability of the rural industrialization process. In the next stage, this adaptive capacity becomes a supporting capacity in facing social change.